2012
DOI: 10.4028/www.scientific.net/amr.585.354
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Tensile Fracture Mechanism of Rheocast A356 Al Alloy Using Cooling Slope

Abstract: A356 aluminium alloy has a wide applicability in the manufacturing of automotive parts. Cooling slope (CS) rheocasting process has been used in the present work to produce A356 billets having near spherical morphology of primary Al phase. Absence of dendritic primary phase, observed in case conventionally cast A356 alloy, and finer distribution of secondary eutectic Si phase within the matrix establishes the usefulness of the CS casting route. Near spherical primary phase in the rheocast alloy ensures better s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 6 publications
1
20
1
Order By: Relevance
“…The present finding is in contradiction with most of the previous studies (Table 1) which shows a minimum grain size and maximum shape factor at higher cooling slope angles [4,[11][12][13][14][15]. The experimental investigations by Taghavi et al [11] and Das et al [4,12,15] concluded 40°(slope length of 400 mm) and 60°angle (slope length of 500 mm) to be the optimum cooling slope angle respectively. Also, Nourouzi et al [13] reported 60°t o be the optimum angle by using genetic algorithm.…”
Section: Microstructural Characterizationcontrasting
confidence: 83%
See 1 more Smart Citation
“…The present finding is in contradiction with most of the previous studies (Table 1) which shows a minimum grain size and maximum shape factor at higher cooling slope angles [4,[11][12][13][14][15]. The experimental investigations by Taghavi et al [11] and Das et al [4,12,15] concluded 40°(slope length of 400 mm) and 60°angle (slope length of 500 mm) to be the optimum cooling slope angle respectively. Also, Nourouzi et al [13] reported 60°t o be the optimum angle by using genetic algorithm.…”
Section: Microstructural Characterizationcontrasting
confidence: 83%
“…Figure 3 shows the variation of grain size and shape factor in Al-7Si alloy with respect to cooling slope angle. The average grain size (CD = 2 ffiffi ffi A p q ) and shape factor (SF = 4pA P 2 ) were calculated using equations mentioned [12], where, A and P represent the area and perimeter of aAl phase, respectively.…”
Section: Microstructural Characterizationmentioning
confidence: 99%
“…The solidified strip and the morphology of A356 alloy on CS strip at exit end, poured at 60° angle is shown in figure 6. (2), reported elsewhere [11,12]. The variation of Grain size and S.F of α-Al phase of A356 alloy at different processing conditions is shown in figure 8.…”
Section: Microstructural Investigation Of A356 Alloymentioning
confidence: 79%
“…Their results indicated that 40° and 40 cm condition is optimum inclined plate angle and length presenting the minimum grain size of 28μm and maximum shape factor of 0.70 with highest uniformity. Das et al [12] has conducted experiments and studied the effects of slope angle and addition of grain refiner on microstructure evolution of the solidifying melt through rheocasting process employing cooling slope (CS) casting route. They reported that there is a significant increase in the tensile properties of the rheocast feed stock processed by CS casting route.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that hardness can be improved by decreasing the re-heating temperature of semi-solid A356 [19]. In addition, increase in cooling rate by cooling slope of a rheo-cast A356 alloy also produced near spherical structures, which enhance tensile strength compared to dendritic structures produced by gravity casting [20]. Figure 8b,c shows thixoformed samples and microstructures at the center of a thixoformed slug of A356/15%SiC-37µm and A356/15%SiC-15µm, respectively, indicating increased particle size and decreased segregation of the solid phase.…”
Section: Semi-solid Stir-castingmentioning
confidence: 99%